Second Five Year Plan Industry and Transport - Planning Commission, Government of India (Planning Commission, Government of India, 1956)
The first plan provided for systematic and detailed investigation and surveys by the Geological Survey of India, the Indian Bureau of Mines and the National Laboratories with a view to quantitative and qualitative assessment of the country's reserves of important minerals. A sum of Rs. 1 crore was allotted for the expansion of the Geological Survey of India and the Indian Bureau of Mines which was subsequently increased to about Rs. 2:5 crores to enable them to expand more rapidly.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Second Five Year Plan- Industry and Transport; Administration